A 10‐year retrospective survey of acute childhood osteomyelitis in Stockholm, Sweden. (11th August 2020) - von Heideken, Johan; Bennet, Rutger; Eriksson, Margareta; Hertting, Olof
Abstract : Aim: Children with osteomyelitis present with a range of signs and symptoms and with varying degree of severity. The purpose of this study was to provide data on a population‐based 10‐year material of children with acute osteomyelitis. Methods: All children, 0–14 years in Stockholm Region with acute osteomyelitis hospitalised in July 2005–June 2015, were retrospectively studied. Time to hospital presentation, disease localization, inflammation markers, imaging procedures, microbiology, severity classified by the presence of complications, surgical procedures, hospital length of stay and seasonal variation were recorded. Results: There were 430 children with acute osteomyelitis; 61% were boys. The incidence per 100 000 person‐years was 11.6; 9.3 in girls and 13.1 in boys. Median age at admission was 2.9 years with no peak later in childhood. Median time from first symptom to diagnosis was 4 days (range 1–21) and 48% of the cases were localised to femur or tibia. Mean C‐reactive protein was 59 mg/L (range 1–376). Blood ( n = 82) or tissue cultures ( n = 54) were positive in 118 (28%) children. The most common pathogen was Staphylococcus aureus ( n = 88) followed by Streptococcus pyogenes ( n = 12). Surgery was performed in 71 children (17%). There was no mortality. Severe complications were seen in 14 (3.3%) children, five of whom were admitted to intensive care. Median hospital length of stay was 4 days (range 1–60). Conclusions: Osteomyelitis in children is a diagnostic challenge with a low yield of positive bacterial cultures. Few children with uncomplicated disease need surgery, but the risk of severe complications is not negligible.